STRATEGIC MANAGEMENT OF POST-WAR TOURISM INFRASTRUCTURE RECOVERY BASED ON SUSTAINABLE DEVELOPMENT AND SLOW TOURISM - Obolentseva, Larysa (Current Problems of Sustainable Development, 2026)
The article examines post-war recovery of tourism infrastructure as a managed process of sustainable territorial development rather than only as the rebuilding of damaged facilities. The relevance of the study for Ukraine is determined by the uneven return of tourism activity, which will depend on safety, infrastructure readiness, institutional capacity, environmental vulnerability and the attitude of local communities. The article argues that a simple return to pre-war tourism growth models may create additional risks for destinations that have not yet restored their social, ecological and managerial stability. Slow tourism is considered as a strategic approach that supports gradual reopening, longer stays, local consumption, careful interpretation of places and a more balanced relationship between visitors and residents. The proposed management logic connects post-war recovery, a policy matrix and a system of indicators. The policy matrix includes access regulation, advance booking, local tourism fees, seasonality management, local slow routes, community participation and monitoring. The practical value of the study lies in offering a framework that can be adapted by local authorities, destination management organizations and territorial communities while preparing post-war tourism recovery strategies.
Keywords: strategic management, post-war recovery, tourism infrastructure, sustainable development, slow tourism, policy matrix, resilience